The Effects Of The Fränkel's Functıon Regulator (Fr-3) On The Soft Tıssu-E Profıle - Sönmez Fıratlı; Mustafa Ülgen (Galenos Yayinevi, 1995)
The purpose of this study was to examine the effects of the FR-3 appliance on the soft tissue profile. The treatment group consisted of 20 patients with Class HI malocclusion, who were treated with the FR-3 appliance for a mean of 1.9±0.3 years. The control group consisted of 20 subjects with Class HI malocclusion who were followed by a mean of 1.8±0.4 years. The changes due to treatment were compared with the spontaneous changes in the control group. The results showed that at the end of the treatment period, the hard tissue points on the lower jaw were followed by the soft tissue points. However, the expected changes could not seen on the point A and the upper lip.